Short term outcome of midline laparotomies in view abdominalfascia closer - Gandhi, Chinmay S.; Mote, Dajiram G.; Shivani, Zahid; Sama, Kalyan Kumar (International Surgery Journal, 2021)
Background: This is a prospective non randomized observational comparative study for surgical site infections and surgical site occurrences after laparotomy fascia closer with two different techniques. Regular bite remains the standard of care in most hospitals. Laparotomies were done for elective and emergency cases. Methods: There were two techniques used to close abdominal wall fascia. The present study has evaluated small bite abdominal closer verses regular bite closer. Author and his team had used small bite fascia closer technique for all laparotomies, while other group of surgeons utilized regular bite fascia closer. Results: Out of 26 laparotomies in short bite closer, 8 had surgical site infections and surgical site occurrences, while 26 laparotomies in regular bite closer group had 15 patients with surgical site infections and surgical site occurrences. There is significant reduction in surgical site infection and surgical site occurrences observed in small bite abdominal closer group. Conclusions: It is recommended all laparotomies elective or emergent should be closed with small bite technique as it reduces surgical site infections and surgical site occurrences.